2019
DOI: 10.1785/0220190199
|View full text |Cite
|
Sign up to set email alerts
|

Aftershock Analysis of the 2018 Mw 7.1 Anchorage, Alaska, Earthquake: Relocations and Regional Moment Tensors

Abstract: The 30 November 2018 magnitude 7.1 Anchorage earthquake occurred as a result of normal faulting within the lithosphere of subducted Yakutat slab. It was followed by a vigorous aftershock sequence with over 10,000 aftershocks reported through the end of July 2019. The Alaska Earthquake Center produced a reviewed aftershock catalog with a magnitude of completeness of 1.3. This well‐recorded dataset provides a rare opportunity to study the relationship between the aftershocks and fault rupture of a major intrasla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 49 publications
5
22
0
Order By: Relevance
“…3b), we found that the southern and northern clusters dip with angles of ~ 30° and ~ 60°, respectively. These dip angles are consistent with those of the two nodal planes in the focal mechanisms for the mainshock and aftershocks (Ruppert et al 2020). The mainshock hypocenter is likely on the plane of the southern cluster rather than on that of the northern cluster.…”
Section: Conjugate Fault Geometry Based On the Relocated Aftershock Dsupporting
confidence: 82%
See 3 more Smart Citations
“…3b), we found that the southern and northern clusters dip with angles of ~ 30° and ~ 60°, respectively. These dip angles are consistent with those of the two nodal planes in the focal mechanisms for the mainshock and aftershocks (Ruppert et al 2020). The mainshock hypocenter is likely on the plane of the southern cluster rather than on that of the northern cluster.…”
Section: Conjugate Fault Geometry Based On the Relocated Aftershock Dsupporting
confidence: 82%
“…These facts suggest that the Anchorage mainshock was an event with two conjugate faults corresponding to the two aftershock clusters. The suggestion of Ruppert et al (2020) that there are no systematic differences in the focal mechanisms between the southern and northern aftershock clusters also supports this fault con guration.…”
Section: Conjugate Fault Geometry Based On the Relocated Aftershock Dsupporting
confidence: 58%
See 2 more Smart Citations
“…The mainshock and aftershocks generally become deeper after the relocation ( Figure S2). Our relocated mainshock hypocenter is shallower and more eastward than those determined with the double-difference location method (Ruppert et al, 2020) and the finite-fault inversion (C. Liu et al, 2019), partly due to the different velocity models used by these studies. The different colors of the dots in (a) denote focal depths whose scale is shown atop (a), and the sizes of the dots denote magnitudes whose scale is shown beside (a).…”
Section: Methodsmentioning
confidence: 67%